Role of Shleshmatakadhya Agad in the Management of Dushi Visha (International Journal of Ayurveda and Pharma Research, 2025)
Ayurveda is an ancient science that aims to maintain the good health and to cure the diseases and pathological conditions of human beings. Agad tantra is a branch of Ayurveda that deals with the Visha (poison), its associated symptoms along with its Chikitsa (management). In Agad tantra, concept of Viruddhahara (incompatible food/diet), Gara Visha (concocted poison) and Dushi Visha (denatured/latent poison) has been explained in detail that contributes to the leading reasons for the occurrence of toxicity related disorders or disease. Most of the diseases are caused due to unconventional etiology for which Agad tantra comes into focus. To combat the poisonous effect, various Agad Yogas are mentioned in Visha Chikitsa grantha to counteract all types of poisons (Sthawara, Jangama, Kritima visha, Gara visha, Dushi visha). Shleshmatakadhya Agad is one of the Yoga mentioned in Yogaratanakar as a Sarva- vishanashanam under Visha Chikitsa. Shleshmatakadhya agad contains Shleshmatak, Apamarga, Guduchi, Nripdruma, Kantakari and Brihati. This article highlights the role of Shleshmatakadya agad, an antitoxic formulation to conquer diseases due to unconventional etiology in current scenario.